Financial Soundness of Cement Industry of Bangladesh: An Empirical Investigation Using Z-score - Mizan, A. N. K.; Hossain, Md. Mahabbat (American Journal of Trade and Policy, 2014)
For measuring the financial health of a business firm, there are lots of techniques available. But the Altman’s Z-score has been proven to be a reliable tool across contexts. Bangladesh cement industry is a unique one because, the industry is producing a higher amount of cement than the local demand having no supply of local raw materials. The main objective of the study is to assess the fundamental financial health of this industry using Z-score model. All listed cement firms are considered in this study. The required information has been collected from the annual reports of the selected companies and from other sources. The study revealed that two firms, Heidelberg cement and Confidence Cement, are financially sound whereas other three are not in a good position. The findings of the study can be useful for the managers to take financial decision, the stockholders to choose investment options and others to look after their interest in the concern cement manufacturers of the country.
Keywords: Cement industry; Financial soundness; Prediction; Z-score